Synthesis and applications of 4-substituted 1-(4-iodophenyl)pyrrolidine-2, 5-diones. Issue 28 (8th July 2015) - Ali, Bakhat; Shamim, Anwar; Vasconcelos, Stanley N.S.; Stefani, Hélio A.
Graphical abstract: Abstract: The synthesis of 4-substituted 1-(4-iodophenyl)pyrrolidine-2, 5-dione derivatives was achieved through an addition reaction between amines and a thiol in the presence of PMDTA as a base and a copper salt. The derivatives containing a terminal acetylene moiety were converted to the corresponding 1, 4-triazolyl derivatives. The 1-(4-iodophenyl)pyrrolidine-2, 5-dione derivatives were functionalized through oxidation alkylation and allylation reactions. In general, the compounds were obtained in moderate-to-good yields.